2003
DOI: 10.1136/heart.89.6.610
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of ventilation during exercise in chronic heart failure

Abstract: Objective: To determine the pattern of the abnormal ventilatory response in heart failure and how it relates to symptoms by looking at tidal volume (VT) and frequency (f) during exercise. Methods: 45 patients with heart failure and 21 controls underwent maximal treadmill based exercise testing with metabolic gas exchange analysis. The relation of ventilation (V E) to VT was plotted to look for an inflection point where VT failed to increase further. The slope of the relation before this inflection point was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 32 publications
2
30
0
1
Order By: Relevance
“…BNP concentration increases as CHF becomes more severe, and BNP is a known, independent factor of mortality of CHF 19) . Because BNP concentration in our study increased as NYHA functional class increased, 22) . Ventilation perfusion mismatch, impaired diffusion of metabolic gases, respiratory muscle weakness, and heightened sensitivity of peripheral receptors have all been postulated as possible causes 22) .…”
Section: O2 and Vmentioning
confidence: 99%
See 1 more Smart Citation
“…BNP concentration increases as CHF becomes more severe, and BNP is a known, independent factor of mortality of CHF 19) . Because BNP concentration in our study increased as NYHA functional class increased, 22) . Ventilation perfusion mismatch, impaired diffusion of metabolic gases, respiratory muscle weakness, and heightened sensitivity of peripheral receptors have all been postulated as possible causes 22) .…”
Section: O2 and Vmentioning
confidence: 99%
“…Because BNP concentration in our study increased as NYHA functional class increased, 22) . Ventilation perfusion mismatch, impaired diffusion of metabolic gases, respiratory muscle weakness, and heightened sensitivity of peripheral receptors have all been postulated as possible causes 22) . In this way, physiological outcomes such as peak V With regard to another important outcome, indices of HRQOL also decreased with NYHA functional class.…”
Section: O2 and Vmentioning
confidence: 99%
“…Contributory factors include: premature metabolic acidaemia (reflecting reduced O 2 delivery and/or utilisation) [146,147]; increased physiological dead space [4]; increased sympathetic system activation via mechano-or pressor-receptor stimulation in the exercising muscles [148][149][150][151][152] and, possibly, contributions from cardiopulmonary vagal and sympathetic reflexes [132,153,154]. Several studies have shown that breathing pattern in CHF is more rapid and shallow than in healthy controls at any given V9E [4,155,156].…”
Section: Ventilatory Abnormalitiesmentioning
confidence: 99%
“…Hyperventilation is observed at each level of exercise compared with controls. The pattern is also different with increased breathing rate and decreased tidal volume [43]. Exertional dyspnea is far from being only related to pulmonary wedge pressure and has been related to CO 2 output, pulmonary dead space, pulmonary blood flow, and activation of peripheral muscle chemoreceptors.…”
Section: Abnormalities Of the Ventilatory Responsementioning
confidence: 96%